ADJECTIVE PHRASES IN THE PREFACE OF AL-MUNJIDU DICTIONARY FIRST PRINTING WORKS LOUIS MA'LÅªF AL-YASÅª'I: SYNTAX ANALYSIS - Fiddienika, Arief (Universitas Negeri Makassar, 2020)
Abstract. A discussion of Arabic syntax in this study focused on the adjective phrase in a text Preface of Al-Munjidu Dictionary First Printing Works Louis Ma'lu>f Al-Yasu>'i. This study reveals whether in the text there are several types of adjective phrases in the text, how the differences of the adjective phrase is found, and how the functions of the adjective phrases in a sentence, and how to form